Estas terras e seus donos: políticas de especialidades e territorialidade em La Cruz e no mundo guarani missioneiro (1629 - 1828) - Serres, Helenize Soares (2012)
A study about the existing relations between the estancias (ranchs) and the pueblos (villages) in the Jesuitic mission s context. It is an attempt to understand how did those relations worked, in the specific case of the estancia of La Cruz, at the eastern bank of Uruguay river situated in the western border of the present time State of Rio Grande do Sul, Brazil and the pueblo of La Cruz, at the westerns bank of the same river situated at the present time province of Corrientes, Argentina, in the period from 1629 to 1828. On the perspective of the colonial administration of the Spanish America and of the Roman Catholic Church, in this territory, was possible to understand and discuss the organization and the internal production of the whole Jesuitic Province of Paraguay and, especially, of the pueblo of La Cruz and its estancia. The relations of the pueblo of La Cruz with the charrua and minuano nations, in a territory allegedly belonged to the Spanish crown, were also referred, taking on account aspects applicable to the concepts of frontier, border, space and region. Equally was treated the role of the Jesuitic mission estancias in the territory of the so called Missões Orientais do Uruguai, with special attention to the estancia of La Cruz, in a period of many diplomatic issues between the two Iberic crowns, over quarrels which determinated approximation and estrangement with the indigenous population